Posterior extension of beaded juxta-clavicular lines - Narayanan, Nikita; K. S., Keerthana; Thomas, Jayakar (International Journal of Research in Dermatology, 2025)
Juxta-clavicular beaded lines are a dermatological condition that typically appears during puberty. It is also called as cutis punctata lineraris colli. It presents as an asymptomatic, linear papular eruption, predominantly affecting the neck and supraclavicular regions. This condition is more commonly seen in individuals of African descent compared to Caucasians, with a notable female predominance. While the exact cause remains unclear, it is thought to be associated with hormonal changes during puberty. Here we presented a case report on a 28-year-old male with juxta clavicular beaded lines over the neck, extending to the back.